If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (W + 12)(w + -2) = 0 Reorder the terms: (12 + W)(w + -2) = 0 Reorder the terms: (12 + W)(-2 + w) = 0 Multiply (12 + W) * (-2 + w) (12(-2 + w) + W(-2 + w)) = 0 ((-2 * 12 + w * 12) + W(-2 + w)) = 0 ((-24 + 12w) + W(-2 + w)) = 0 (-24 + 12w + (-2 * W + w * W)) = 0 (-24 + 12w + (-2W + wW)) = 0 Reorder the terms: (-24 + -2W + 12w + wW) = 0 (-24 + -2W + 12w + wW) = 0 Solving -24 + -2W + 12w + wW = 0 Solving for variable 'W'. Move all terms containing W to the left, all other terms to the right. Add '24' to each side of the equation. -24 + -2W + 12w + 24 + wW = 0 + 24 Reorder the terms: -24 + 24 + -2W + 12w + wW = 0 + 24 Combine like terms: -24 + 24 = 0 0 + -2W + 12w + wW = 0 + 24 -2W + 12w + wW = 0 + 24 Combine like terms: 0 + 24 = 24 -2W + 12w + wW = 24 Add '-12w' to each side of the equation. -2W + 12w + -12w + wW = 24 + -12w Combine like terms: 12w + -12w = 0 -2W + 0 + wW = 24 + -12w -2W + wW = 24 + -12w Reorder the terms: -24 + -2W + 12w + wW = 24 + -12w + -24 + 12w Reorder the terms: -24 + -2W + 12w + wW = 24 + -24 + -12w + 12w Combine like terms: 24 + -24 = 0 -24 + -2W + 12w + wW = 0 + -12w + 12w -24 + -2W + 12w + wW = -12w + 12w Combine like terms: -12w + 12w = 0 -24 + -2W + 12w + wW = 0 The solution to this equation could not be determined.
| 2x+3x+1=16 | | 2(4)+3(2)(-4)-4(16)= | | y=-8+-1t+-2x+0.5x^2 | | y=0.5x^2+2x-8-4x-t | | 2(x+3)-7=9 | | (4x-5)/4-(2x-1)/6=x | | (2x-4)+(6-x)=0 | | 3(x-1)-4(2x+3)=5 | | (3-x)/6=x/3 | | 3-x/6=x/3 | | (3x^2+5)-(x^2-4x+5)=0 | | 8x^3-104x=0 | | 0.5x^2+2x-8-4x-t=0 | | (m/2)-√5=3 | | (6*5)+3x+22-3x=52 | | xi-6x+5=0 | | (6*5)+(22-1y)+1y=52 | | 15+(0.75x)=y | | (2x-y)=z | | 25i^2-4=0 | | xi+14x+45=0 | | 2x+8x=6 | | 90-20x=80 | | (12+6)+1x=3x-12 | | (x^2y^2/x^4y^4)/(xy/x^2y^3) | | xi-6x+5=5 | | 5X^2-Y=10 | | (4u-2)(9-u)=0 | | X^2-1/6x | | -7x+20=3x+100 | | 12+1x+6=3x-12 | | 30=c/28 |